MIGRASI BASISDATA PADA SISTEM INFORMASI AKADEMIK UNIVERSITAS TANJUNGPURA - Muhammad Mudrika Bafadal (SISFOTENIKA, 2012)
Abstract : Information system is a computer-based components and manuals designed to collect, store and manage data and provide output information to the users. Tanjungpura University is one public university in Pontianak that have information systems. One of the information system is a system of academic information systems that manage information on student data from the bio-data UNTAN, values, and learning activities. But there is majoring in UNTAN who already have academic information system (SIAKAD), the Department of Electrical Engineering is owned by the engineering faculty only deal with data that is in electrical engineering majors. As for the civil engineering department has entered into SIAKAD UNTAN. Because the electro SIAKAD only runs at local network only, the technique requires a data migration applications from electro to SIAKAD UNTAN SIAKAD. But because there are differences in the structure of databases and database types that exist in both SIAKAD is then needed an application that can move data from Electro to SIAKAD. SIAKAD UNTAN making it easier for electrical engineering students to access data from SIAKAD UNTAN. Because the data has not been a student of electrical engineering at SIAKAD UNTAN. Keywords: information systems, data migration, database, UNTAN, electro, SIAKAD